Improving Mathematics Cognitive Learning Outcomes Through the Application of Bandicam Video to Class X Senior High School Students in Kampar Regency - Yeyen Vioskha (Universitas Riau, 2021)
This research was motivated by the learning outcomes of SMAN 5 Tapung students who were under the target (KKM). This research was to intend providing the solutions by applying Bandicam videos in the learning. The purpose of this study was to improve student learning outcomes on trigonometric comparison material in right triangles using Bandicam video media in class X Mia SMAN 5 Tapung. This study used a quantitative approach with interview observation steps, survey methods and blended learning methods. The research subjects were students of class X MIA SMAN 5 Tapung and the object of this study was the use of videos recorded with the Bandicam application to improve cognitive mathematics learning outcomes. Data collection techniques used tests, observations, and documentation, while data analysis techniques used qualitative descriptive data analysis methods. The average score obtained by students at the end of the first cycle was 67.6 with the number of students who reached the KKM as many as 32 students (43.7%), then at the end of the second cycle the average value of students increased to 77.4 and as many as 32 students scored reaching the KKM (87.5%). By increasing the KKM results obtained after learning using Bandicam video media, the cognitive learning outcomes of students are increased.